Navigating Educational Challenges in Indonesia: Policy Recommendations for Future Success - Sain, Zohaib Hassan; Aulia Luqman AZIZ; Moses Adeolu AGOI (RADINKA JAYA UTAMA PUBLISHER, 2024)
Domestic and international observers scrutinize education in Indonesia due to persistent challenges that significantly diminish its quality. This study aims to provide a constructive analysis by identifying key issues within the Indonesian educational sector and proposing various strategic solutions to enhance the system. Utilizing a qualitative methodology, this research incorporates a literature review along with the collection of both primary and secondary data. The data collection involves extensive documentation and subsequent analysis. The findings reveal multiple pressing issues in Indonesian education, such as disparities in educational outcomes, substandard educational facilities and infrastructure, deficiencies in teacher quality and conduct, issues with student morality, and a lack of tolerance for ethnic diversity. Addressing these problems requires a collaborative effort across all societal sectors. Proposed solutions include enhancing teacher and student welfare, cultivating a global perspective and fostering a positive mindset among educators and learners, designing an inclusive and holistic curriculum, ensuring vigilant management of budgets, and encouraging greater involvement from the private sector. By incorporating these strategies, there is a potential not only to rectify current deficiencies but also to elevate the overall standard of education in Indonesia. This improvement will require sustained efforts and a commitment to innovation and inclusivity in educational practices.